2017
DOI: 10.1177/1469540517736560
|View full text |Cite
|
Sign up to set email alerts
|

Ecological habitus intergenerationally reproduced: The children of Czech ‘voluntary simplifiers’ and their lifestyle

Abstract: The intergenerational reproduction of values and lifestyles has been at the centre of attention for the social sciences for several decades. However, only rarely has this topic been examined from the perspective of environmentally friendly lifestyles. In this article, we build on unique longitudinal research that includes generations of parents and children from Czech ‘voluntarily simple’ families. Drawing on sociological theories of consumption and the Bourdieusian concept of habitus, we deal with the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…The New Colourful interpret their life paths as a result of a gradual transformation of their lifestyle based on their faithfulness to their values, not as a radical lifestyle transformation, like in the case of the 'back to the land movement' [see Elgin 1981: 20] or the 'simplicity movement' [see Alexander and Ussher 2012: 8]. Overall, these findings suggest 22 The other research findings of our team, regarding the relatively successful intergenerational reproduction of the Colourful's habitus to their children, suggest that higher cultural capital could facilitate the reproduction of a modest way of life [for more on these results, see Pelikán et al 2017]. 23 Bourdieu understands habitus as a nonlinear process, which, while being anchored in class, also grows out of imitation and one's personal experience, thus opposing, with regard to consumption, the perspective of homo oeconomicus [1984: 183].…”
mentioning
confidence: 77%
“…The New Colourful interpret their life paths as a result of a gradual transformation of their lifestyle based on their faithfulness to their values, not as a radical lifestyle transformation, like in the case of the 'back to the land movement' [see Elgin 1981: 20] or the 'simplicity movement' [see Alexander and Ussher 2012: 8]. Overall, these findings suggest 22 The other research findings of our team, regarding the relatively successful intergenerational reproduction of the Colourful's habitus to their children, suggest that higher cultural capital could facilitate the reproduction of a modest way of life [for more on these results, see Pelikán et al 2017]. 23 Bourdieu understands habitus as a nonlinear process, which, while being anchored in class, also grows out of imitation and one's personal experience, thus opposing, with regard to consumption, the perspective of homo oeconomicus [1984: 183].…”
mentioning
confidence: 77%
“…Several qualitative studies disentangle the processes involved in the transmission of environmental practices within families (Gentina and Muratore, 2012;Collins, 2015;Gentina and Singh, 2015;Gram and Grønhøj, 2016;Pelikán et al, 2020). A special issue of Families, Relationships, and Societies discussed various dimensions of environmentalism within and beyond families (for example, Boddy et al, 2016;Jamieson, 2016).…”
Section: Igt Of Environmental Practices and Its Underlying Processesmentioning
confidence: 99%
“…In line with the idea of centrifugal forces, we identify a declining involvement across generations (see also Figure 1). Although environmental practices of family members resemble each other, they decline in frequency and engagement due to period and time differences, and possibly the impact of age (Krahn and Galambos, 2014;Pelikán et al, 2020). While G1 revealed a high degree of environmental engagement, G3 admits that in some circumstances convenience and lifestyle preferences surpass habitual environmentally friendly action.…”
Section: Top-down Transmission With Declining Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1990s, qualitative studies on the voluntary modesty of Czech households revealed their motivations, as well as practices they developed (Librová, 1994). A recent continuation of this research, which interviewed children of these families from the 1990s, further analysed how the habitus was acquired in the family and the environmental values which have been reproduced throughout their lives (Kala et al, 2017; Pelikán et al, 2020). Yet, several studies point out that different sustainable everyday practices have been historically present in this part of Europe, although there are not necessarily motivated by environmental sensitivity, such as, for example, growing food.…”
Section: Everyday Responses To Climate Change In the Czech Contextmentioning
confidence: 99%